Utilization of Digital Marketing for Micro, Small, and Medium Enterprises (UMKM) Affected by the Covid-19 Pandemic in Gubeng District, Surabaya City - Dwi Suhartini; Gusti Dian Prayogi; Fajar Syaiful Akbar (Future Science, 2021)
UMKM is a small and informal business organization that drives the national economy. However, the COVID-19 pandemic had an impact on the sustainability of the UMKM creative industry business in the Gubeng District, Surabaya City. This business has a great opportunity because consumers prefer to make purchases online due to the implementation of social distancing. The problem faced by local UMKM is that product marketing still uses conventional methods by offering limited products only to friends and the closest environment or by word of mouth so that during the social distancing period, it hampers the reach of marketing its products. For this reason, this service program conducts online marketing training and assistance to 20 participants with one of the marketplaces that are well known to the public, namely the shop platform. The service program had a positive effect, around 60% can apply Shopee activation and the other 40% have not been able to apply, this is because most of the participants are Generation X mothers who are less familiar with information technology. However, all participants were very enthusiastic about learning even though many were constrained by the PPKM (Restrictions on Community Activities) regulations.